Non-classical Immunity Controls Microbiota Impact on Skin Immunity and Tissue Repair - Linehan, Jonathan L.; Harrison, Oliver J.; Han, Seong-Ji; Byrd, Allyson L.; Vujkovic-Cvijin, Ivan; Villarino, Alejandro V.; Sen, Shurjo K.; Shaik, Jahangheer; Smelkinson, Margery; Tamoutounour, Samira; Collins, Nicholas; Bouladoux, Nicolas; et al. (Cell, 2018)
Mammalian barrier surfaces are constitutively colonized by numerous microorganisms. We explored how the microbiota was sensed by the immune system and the defining properties of such responses. Here, we show that a skin commensal can induce T cell responses in a manner that is restricted to non-classical MHC class I molecules. These responses are uncoupled from inflammation and highly distinct from pathogen-induced cells. Commensal-specific T cells express a defined gene signature that is characterized by expression of effector genes together with immunoregulatory and tissue-repair signatures. As such, non-classical MHCI-restricted commensal-specific immune responses not only promoted protection to pathogens, but also accelerated skin wound closure. Thus, the microbiota can induce a highly physiological and pleiotropic form of adaptive immunity that couples antimicrobial function with tissue repair. Our work also reveals that non-classical MHC class I molecules, an evolutionarily ancient arm of the immune system, can promote homeostatic immunity to the microbiota. Microbiota induce a form of adaptive immunity that couples antimicrobial function with tissue repair.
CRIS-Team Scopus Importer:2022-12-14
Keywords: H2-M3; MHCIb; microbiota; non-classical MHC class I; skin immunity; Staphylococcus epidermidis; tissue repair